Exclusive Breastfeeding Practice and Maternal Employment among Mothers of Infants: A Comparative Cross-Sectional Study - Shrestha, Rubina; Chhetri, Pradip; Priyanka, Jyoti; Bhusal, Chet Kant (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Exclusive breastfeeding (EBF) practices during first six months of life are the most cost-effective intervention for reducing infant and child morbidity and mortality. However, adherence to EBF practices in developing countries remains unsatisfactory, where maternal employment has been identified as one of the influencing factor. The study aims to identify and compare EBF practices and its factors influencing among employed and unemployed mothers. MATERIALAND METHODS An institutional based comparative cross-sectional study was conducted among 362 mothers of infants visiting the immunization clinic of Universal College of Medical Sciences, Bhairahawa, Nepal, from December 2020 to March 2021 following ethical clearance (UCMS/IRC/114/20) and verbal consent from participants. Descriptive statistics was used to compare EBF practices and multivariate logistic regression to identify independent predictors of EBF. RESULTS Total 362 (181 employed and 181 unemployed) mothers were interviewed. Prevalence of EBF was 13.8% and 81.2% among employed and unemployed mothers respectively. Further EBF practice had significant association with working status of mothers (AOR= 15.44, 95% CI 6.76-35.25) and monthly family income (AOR=3.31, 95% CI 1.24-8.84). Among employed, EBF practice had significant association with carry infant to work place (AOR= 12.36, 95% CI 4.35-49.87) whereas type of delivery (AOR= 3.88, 95% CI 1.69-8.90) was significantly associated among unemployed mothers. CONCLUSION EBF practices among employed mothers were less than that of unemployed mothers. Provisions to provide additional supports, either by revising the period of maternity leave or adopting different alternatives to prolong the period of EBF may be beneficial for employed mothers and their children.